Pharmacokinetics of norfloxacin after intravenous, intramuscular and subcutaneous administration to rabbits. Issue 1 (11th June 2017) - Marín, P.; García‐Martínez, F.; Hernándis, V.; Escudero, E.
Abstract : The disposition kinetics of norfloxacin, after intravenous, intramuscular and subcutaneous administration was determined in rabbits at a single dose of 10 mg/kg. Six New Zealand white rabbits of both sexes were treated with aqueous solution of norfloxacin (2%). A cross‐over design was used in three phases (2 × 2 × 2), with two washout periods of 15 days. Plasma samples were collected up to 72 hr after treatment, snap‐frozen at −45°C and analysed for norfloxacin concentrations using high‐performance liquid chromatography. The terminal half‐life for i.v., i.m. and s.c. routes was 3.18, 4.90 and 4.16 hr, respectively. Clearance value after i.v. dosing was 0.80 L/h·kg. After i.m. administration, the absolute bioavailability was (mean ±  SD ) 108.25 ± 12.98% and the Cmax was 3.68 mg/L. After s.c. administration, the absolute bioavailability was (mean ±  SD ) 84.08 ± 10.36% and the Cmax was 4.28 mg/L. As general adverse reactions were not observed in any rabbit and favourable pharmacokinetics were found, norfloxacin at 10 mg/kg after i.m. and s.c. dose could be effective in rabbits against micro‐organisms with MIC ≤0.14 or 0.11 μg/mL, respectively.